2005
DOI: 10.1002/hup.665
|View full text |Cite
|
Sign up to set email alerts
|

Lithium and valproate attenuate dextroamphetamine-induced changes in brain activation

Abstract: These results suggest that both lithium and valproate can significantly attenuate dextroamphetamine-induced changes in brain activity in a task dependent and region specific manner. This is the first human evidence to suggest that both lithium and valproate may have a similar effect on regional brain activation, conceivably via similar effects on PI-cycle activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Both treatment groups had a significant decrease in BOLD signal during the word generation paradigm after treatment, compared with the placebo group. Previously our research group has shown that lithium and valproate exert task and region dependent effects on dextroamphetamine-induced changes in brain activation (Bell et al, 2005). The current study demonstrates that lithium and valproate, alone, exert differential effects on brain activity in healthy control subjects.…”
Section: Discussionmentioning
confidence: 55%
“…Both treatment groups had a significant decrease in BOLD signal during the word generation paradigm after treatment, compared with the placebo group. Previously our research group has shown that lithium and valproate exert task and region dependent effects on dextroamphetamine-induced changes in brain activation (Bell et al, 2005). The current study demonstrates that lithium and valproate, alone, exert differential effects on brain activity in healthy control subjects.…”
Section: Discussionmentioning
confidence: 55%
“…According to this study, the inhibition of activity of citrate synthase may be probably related to the pathophysiology of this disease [36]. There are some studies showing that amphetamine induces changes in various systems, such as signaling pathways and kinases and phosphatases activities, and that mood stabilizers prevent and/or reverse some of these biochemical and other behavioral effects caused by amphetamine [37][38][39][40][41].…”
Section: Bipolar Disordermentioning
confidence: 84%
“…Despite of the well-recognized limitations of animal models of bipolar disorder in terms of face validity (Machado-Vieira et al, 2004;Einat et al, 2000), it is well known that AMPH induces manic symptoms in BD patients (Anand et al, 2000) as well as in healthy volunteers (Strakowski and Sax, 1998). Using fMRI, Bell et al (2005) reported that Li and VPT attenuated AMPH-induced changes in human brain during neuropsychological tasks. In addition, Beaulieu et al (2004) recently found that the hyperactivity induced by AMPH is partially mediated by Akt/glycogen synthase kinase-3β (GSK-3β) signaling pathway and that Li was able to reverse this effect.…”
Section: Discussionmentioning
confidence: 98%